2022
DOI: 10.1136/bmjopen-2022-066066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of functional relaxation on the quality of life in patients with periprosthetic joint infection: Protocol for a randomised controlled trial

Abstract: IntroductionPeriprosthetic joint infection (PJI) is a devastating complication in orthopaedic and trauma surgery, which puts a high burden on the patients involving recurrent hospitalisation, prolonged courses of antibiotic medication, severe pain and long periods of immobility as well as high levels of psychological distress. Thus, this multicentre study aims at implementing body-oriented psychotherapy in clinical practice and evaluating its therapeutic effect on the quality of life.Methods and analysisA pros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…While research on the effect of psychological interventions in this population is scarce, these findings highlight the need to integrate psychological support in daily clinical care for patients with implant-associated infections ( Kunutsor et al, 2017 ). For instance, weekly group sessions incorporating easily applicable methods such as functional relaxation or breathing exercises could be beneficial in improving the patients’ quality of life ( Zaccaro et al, 2018 ; Walter et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research on the effect of psychological interventions in this population is scarce, these findings highlight the need to integrate psychological support in daily clinical care for patients with implant-associated infections ( Kunutsor et al, 2017 ). For instance, weekly group sessions incorporating easily applicable methods such as functional relaxation or breathing exercises could be beneficial in improving the patients’ quality of life ( Zaccaro et al, 2018 ; Walter et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects of mind–body interventions, and especially mindfulness meditations are widely reported for a range of diseases ( Sampaio et al, 2017 ). While the effect of such an adjunct therapy approach has still to be evidenced in FRI patients ( Walter et al, 2022a ), improvements in functional outcomes were reported in patients undergoing primary arthroplasty procedures after relaxation exercise ( Lim et al, 2014 ; Eymir et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%